Derecho de la competencia de la UE y derecho fiscal: la metodología de comparación intraramas aplicada a la evaluación de los precios injustos - Angulo Garzaro, Noemí; Angulo Garzaro, Amaya (Revista Chilena de Derecho, 2019)
Price has an undeniable importance for market operators. Changes operated in the legal environment may have an unanticipated impact on prices; therefore, regulators must be cautious when designing legal tools to assess the adequacy to legality of pricing practices, that is, when evaluating whether a given price is to be regarded as ‘fair’.This paper finds that, from all the branches of a legal system, it is for tax law and competition law to have the highest impact on prices when monitoring the fairness of prices charged by enterprises op- erating in the market. By conducting a comparative analysis on the mechanisms used by the administrative authorities active in both branches of law it identifies the synergies that, tran- scending the divergences, lead one of the branches to learn from the experience of the other